What You See is What They Get: Protecting users from unwanted use of microphones, cameras, and other sensors - Howell, Jon; Schechter, Stuart (Web 2.0 Security and Privacy, 2010)
Sensors such as cameras and microphones collect privacy-sensitive data streams without the user's explicit action. Conventional sensor access policies either hassle users to grant applications access to sensors or grant with no approval at all. Once access is granted, an application may collect sensor data even after the application's interface suggests that the sensor is no longer being accessed. We introduce the sensor-access widget, a graphical user interface element that resides within an application's display. The widget provides an animated representation of the personal data being collected by its corresponding sensor, calling attention to the application's attempt to collect the data. The widget indicates whether the sensor data is currently allowed to flow to the application. The widget also acts as a control point through which the user can configure the sensor and grant or deny the application access. By building perpetual disclosure of sensor data collection into the platform, sensor-access widgets enable new access-control policies that relax the tension between the user's privacy needs and applications' ease of access.